An Interface for Linking Ancient Languages - Mallia Michele; Bandini Michela; Quochi Valeria (Cybernetics and Information Technologies)
This paper focuses on the linking potentials offered by the EpiLexO web-based front-end for creating and editing an ecosystem of digital resources for ancient languages, developed in the context of a project on the languages of fragmentary attestation of ancient Italy. The focus is particularly on mechanisms introduced for linking lexical information to other information bits either internally or externally, e.g., for creating attestations by linking lexical forms to their variants in relevant inscriptions, as well as for linking lexical data to external independent LOD datasets available on a remote endpoint. Finally, in the conclusions, we briefly introduce some future planned or desired enhancements as well as the final platform component, a parallel interface that constitutes the fruition application, which will be open to anyone on the web and will allow for browsing, searching, cross-querying and visualizing the created set of interlinked resources.